Determination of functional strength imbalance of the lower extremities - Newton, R. U.; Gerber, A.; Numphuis, S.; Shim, J. K.; Doan, B. K.; Robertson, M.; Pearson, D. R.; Craig, B. W.; Häkkinen, K.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 2006)
The purposes of this study were (a) to determine whether a significant strength imbalance existed between the left and right or dominant (D) and nondominant (ND) legs and (b) to investigate possible correlations among various unilateral and bilateral closed kinetic chain tests, including a field test, and traditional isokinetic dynamometry used to determine strength imbalance. Fourteen Division I collegiate women softball players (20.2 +/- 1.4 years) volunteered to undergo measures of average peak torque for isokinetic flexion and extension at 60[degrees][middle dot]s-1 and 240°/s; in addition, measures of peak and average force of each leg during parallel back squat, 2-legged vertical jump, and single-leg vertical jump and performance in a 5-hop test were examined. Significant differences of between 4.2% and 16.0% were evident for all measures except for average force during single-leg vertical jump between the D and ND limbs, thus revealing a significant strength imbalance. The 5-hop test revealed a significant difference between D and ND limbs and showed a moderate correlation with more sophisticated laboratory tests, suggesting a potential use as a field test for the identification of strength imbalance. The results of this study indicate that a significant strength imbalance can exist even in collegiate level athletes, and future research should be conducted to determine how detrimental these imbalances could be in terms of peak performance for athletes, as well as the implications for injury risk.